Análises perceptivo-auditiva e acústica de vozes de cantores líricos pré e pós aquecimento vocal - Carolina Ghelli Ferreira de Melo (2013)
Objectives: Compare auditory-perceptive and vocal acoustic parameters of lyric singers pre and post vocal warm-up, developed during the research, in order to demonstrate additional data for the comprehension of the effects of its application in vocal quality and pre-determined acoustic descriptors of these subjects: fundamental frequency (F0), jitter, shimmer, dynamic envelope, attack curve, harmonicity, spectral distribution and variation and centroid spectral. Methods: This research project has experimental character, with quantitative and qualitative delineation. Fourteen lyric singers were evaluated, according to the inclusion-exclusion criteria. Pre and post vocal warm-up, the female participants were requested to emit a sustained vowel Key words: Vocal warm-up; voice quality; voice timbre; professional voice; acoustic analysis; auditory-perceptive analysis. [a], in tone Sol3 (392 Hz) and the male participants in Sol2 (196 Hz), in both cases with intensity mezzo-strong and during 10 seconds; and both were also requested to sing part of a specific musical play, a capella: starting phrases of Ave Maria, of Charles Gounod/Bach. The vocal samples were acoustically analysed by software PRAAT 5.1.32 (BOERSMA e WEENINK, 2010); and auditory-perceptive analysis was performed by two voice specialized speech therapists and two singing teachers, all of them with a minimum of five years of experience in this field, and the parameter evaluated was the vocal quality of singing voice. Results: In general, as for the auditory-perceptive analysis, an agreement of 35.71% was observed, among all of the evaluators, in the choice of samples post vocal warm-up. Out of the global descriptors considered relevant for a comparative statistic analysis, the jitter (0.019) and harmonicity (0.011) were highlighted for showing a clear separation between the groups (relevant index p<0.05). Conclusions: The research achieved relevant results concerning the importance of vocal warm-up in the definition of vocal quality of the lyric singers. The auditory-perceptive test did not show strong correlation with the results of acoustic analysis. Significant statistic results were obtained with the acoustic descriptors jitter and harmonicity. The qualitative discussion over spectral variation and centroid spectral deserve a more specific approach.